Penggunaan Teknik KWL (Know-Want to Know-Learned) dan LRD (Listen-Read-Discuss) untuk Meningkatkan Minat dan Keterampilan Membaca - Mas Diana Larasati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This research focuses on efforts to improve interest and reading skills in Indonesian. The strategies implemented use the KWL (Know–Want to Know–Learned) and LRD (Listen–Read–Discuss) techniques. This type of research is in the form of Classroom Action Research using the Kemmis and McTaggart spiral model. This research was conducted at SD “Mawar” Surabaya with 23 sixth-grade students, the research was conducted from April 2025 to May 2025. The research activities were carried out through two cycles, each consisting of four meetings. Data were obtained through observation, interviews, pre-tests and post-tests, as well as documentation of the learning process. The research instruments include a Lesson Implementation Plan, questionnaires, interest and skills observation sheets, and photo documentation. The research results show that students become more focused during the learning process, demonstrate active involvement in discussions, and have a better understanding of the reading material presented. The KWL technique specifically helps students develop critical thinking skills and fosters the habit of reflecting on the content of the text they have read. The LRD technique provides space for students to collaborate and exchange insights in understanding the reading material. The combination of these two strategies creates a reading learning environment that is not only enjoyable but also meaningful and oriented towards deep understanding.